Students' Critical Thinking Ability in Solving SPLDV Problems with Jumping Task Based on Emotional Intelligence - Lestari, Nurcholif Diah Sri; Hafidhoh, Nabilatul; Putri, Inge Wiliandani Setya; Pambudi, Didik Sugeng; Kurniati, Dian (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2024)
Critical thinking ability is an ability that students must have, using the jumping task method can develop students' critical thinking abilities. In the decision-making process, behavioral control is needed so that students remain confident and motivated to solve a problem optimally. One behavioral control over what a person feels is emotional intelligence. This research aims to describe students' critical thinking abilities in solving jumping task questions on SPLDV material in terms of the students' level of emotional intelligence. This type of research is descriptive qualitative using questionnaires, tests and interviews to collect research data. Three students from class VIII-B at SMPN 7 Jember were chosen as research subjects. The research results show that in solving jumping task questions, students with high emotional intelligence have high critical thinking abilities, students with moderate emotional intelligence have moderate critical thinking abilities, and students with low emotional intelligence have low critical thinking abilities. For students with low emotional intelligence, when faced with difficult problems, they are expected to be able to practice controlling their emotions, convince themselves to always be optimistic, and more practice to communicating so that you can convey information and intentions more clearly and confidently